(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Efficacy of aqueous suspension of Bacillus thuringiensis var. israelesis (Bti) was studiedagainst the laboratory reared 3rd and 4th instar larvae of Aedesaegypti. Mortality rates aswell as histological changes in the larval midgut due to toxic effect of Bti wereinvestigated. Several microscopic techniques were also used to identify the toxic effecton the mosquito larvae. The highest mortality rate (96.66%) was found in case of 3rdinstar larvae at 1.0μl/ml dose where LC50 value was 0.0097. Larval mortalities increasedsignificantly to A. aegypti as doses increased (p< 0.05). Histological study revealed thatcellular layers of the midgut epithelium were intact in control sample, but in case of theBti treated larvae none of these were found in the midgut, only bacterial spores wereseen. Results of the microscopic studies indicated that, among the six different coloniesfound in bacterial cultures, Bti spore, sporangium and vegetative cells were confirmedfrom one colony by phase transition and fluorescent microscopy. The Cry (crystals)endotoxins and Bti spore were confirmed by the SEM. Asiat. Soc. Bangladesh, Sci. 41(1): 33-44, June 2015